Hormonal contraception as a risk factor for obesity (Medical Journal of Indonesia, 2005)
Hormonal contraception is related to change in the metabolism of some nutrients that may lead to an increase in body weight. The aims of this study is to assess the risk of obesity in hormonal contraceptive users in the District of Kulon Progo, Jogjakarta, Indonesia. A cross sectional study was used to determine the prevalence of obesity among users of contraception. A systematic cluster random sampling, using villages as clusters, was used to choose 647 users of contraception in Kulon Progo. A hundred and two obese cases and 102 control, matched-for-age and socioeconomic status, controls were included in the case control study used to evaluate the risk of obesity among users of hormonal contraception. The prevalence of obesity among users of contraception in Kulon Progo was 15.9%. Users of hormonal contraception has a increased risk for obesity, OR: 9.4 (95% CI: 1.1 - 81.5). Users of combination pills faced the highest risk, followed by users of injected progesterone depot, while the risk in implant users was the same as that in users of non-hormonal contraception. The risk of obesity was significantly higher after 7 years of hormonal contraception use. The risk of obesity was neither related to energy intake nor expenditure. The increased risk of obesity in users of hormonal contraception was still significant after controlling for age, parity, initial weight, socioeconomic status, energy intake and expenditure, and parental obesity. We conclude that the risk of obesity is higher in users of hormonal contraception compared to the non-hormonal ones. Users of combination pills face the highest risk of obesity. (Med J Indones 2005; 14: 163-8)